Pretreatment of lignocellulosic biomass waste mixtures using a low-cost ionic liquid - Sanyam Jain; Hari Mahalingam (Sustainable Chemistry for Climate Action)
Pretreatment is a critical step in bioethanol production, impacting both cost and environmental sustainability. Traditional acid and alkali methods are expensive due to the need for costly stainless-steel reactors and pose environmental risks. This study explores a more cost-effective approach using locally available biomass mixtures, reducing the need to source a single type of biomass from distant locations, using Triethylammonium Hydrogen Sulfate ([TEA][HSO4]), a novel, low-cost, and environmentally friendly ionic liquid. [TEA][HSO4] was synthesized & characterized (via FTIR and NMR) and then applied to a mixture of rice straw and sugarcane bagasse in varying ratios (five samples in all, where two were pure biomass and the remaining three were mixtures). The biomass was pretreated at 130°C for 0.5 or 1.0 h, with a 4:1:1 weight ratio of ionic liquid, water, and biomass. The pretreatment's effects were analyzed using FTIR for functional group changes, SEM for effect on surface morphology, and PXRD for alteration in crystallinity. The results revealed significant lignin reduction, especially in sugarcane bagasse, where lignin content dropped from 24.80 to 14.87 wt.% after 1 h of pretreatment. When the pretreatment duration was extended from 0.5 h to 1 h, an increase in crystallinity was more prominent in the biomass mixtures than in the individual biomass samples. Specifically, there was a 0.9% increase for 100 wt% rice straw, a 0.3% increase for 100 wt% sugarcane bagasse, and a 7.1% increase for a 1:1 mixture by weight, attributed to synergistic effects. The most favourable results were achieved with a mixture of 25 wt% rice straw and 75 wt% sugarcane bagasse, attributed to reduced carbohydrate loss, providing useful insights for optimizing enzymatic hydrolysis resulting in improved bioethanol production.